Improving Cognitive Function after Traumatic Brain Injury: A Clinical Trial on the Potential Use of the Semi-Immersive Virtual Reality - Rosaria De Luca; Maria Grazia Maggio; Giuseppa Maresca; Desiree Latella; Antonino Cannavò; Francesca Sciarrone; Emanuele Lo Voi; Maria Accorinti; Placido Bramanti; Rocco Salvatore Calabrò (Behavioural Neurology)
Traumatic brain injury (TBI) is the most common cause of long-term disability and death among young adults, and it represents an enormous socioeconomic and healthcare burden. Our purpose is to evaluate the effects of a virtual reality training with BTs-Nirvana (BTs-N) on the recovery of cognitive functions in TBI subjects, using the interactive semi-immersive program. One hundred patients with TBI were enrolled in this study and randomized into either the Traditional Cognitive Rehabilitation Group (TCRG: n=50) or the Virtual Reality Training Group (VRTG: n=50). The VRTG underwent a VRT with BTs-N, whereas the TCRG received a standard cognitive treatment. Each treatment session lasted 60 minutes and was repeated three times a week for 8 weeks. All of the patients were evaluated by a specific psychometric battery before (T0) and immediately (T1) after the end of the training. VRTG and TCRG had a significant improvement in cognitive functioning and in mood, but only VRTG presented with a significant increase in cognitive flexibility and shifting skills and in selective attention. In conclusion, our results suggest that VR may be a useful and effective approach for the rehabilitation of patients with TBI, leading to better cognitive and behavioral outcomes.